Analisis Implementasi Z-Mijewski Model Sebagai Alat Untuk Mengukur Kerugian Perusahaan Pada PT Gudang Garam Tbk - Ayu Lestari; Sriwardany; Ratna Sari Dewi (Journal of Trends Economics and Accounting Research, 2022)
Loss of a company can be measured through analysis of the company's financial statements. The purpose of this study is to calculate, measure, and analyze predictions of potential losses of PT. Gudang Garam Tbk by using the Z-mijewski model. The subjects in this study were PT. Gudang Garam Tbk and the object in this study are financial report data at PT. Gudang Garam Tbk, namely in the form of income statement and balance sheet for 2015, 2016, and 2017. This research uses a type of qualitative research with a descriptive analysis approach.The results of the research conducted using the Z-Mijewski model show that PT. Gudang Garam Tbk experiences potential losses. In 2015 the value of Z-Mijewski was greater than the value of Z-Mijewski in 2016, and in 2017 the value of Z-Mijewski again increased, but still suffered potential losses